2022
DOI: 10.30742/jikw.v11i1.1441
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Pesticides and Workload on Osteoarthritis Incidence in Farmers: A Narrative Review

Abstract: An osteoarthritis is a group of pathologies in joints that include cartilage degradation, bone remodeling, osteophyte formation, and synovial inflammation which in turn can cause pain, stiffness, swelling, and loss of normal joint function. The increasing prevalence of osteoarthritis is associated with jobs that require physical strength (physically demanding) or heavy work, one of which is agriculture. This is in line with the World Health Organization's statement, farming for 1-9 years increases the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Moreover, according to Muraki et al (2011) reported that workers in agriculture, forestry, and fisheries have the highest prevalence of kneeling, squatting, walking, lifting weights, and carrying heavy loads on their backs (Lidaka et al, 2020). Notably, kneeling and squatting positions are associated with knee OA incidence (Maghfiroh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to Muraki et al (2011) reported that workers in agriculture, forestry, and fisheries have the highest prevalence of kneeling, squatting, walking, lifting weights, and carrying heavy loads on their backs (Lidaka et al, 2020). Notably, kneeling and squatting positions are associated with knee OA incidence (Maghfiroh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Faktor risiko paling berperan terhadap timbulnya keluhan nyeri lutut pada petani adalah beban dan postur kerja, diantaranya adalah mengangkat beban berat, posisi jongkok dan berlutut (Maghfiroh et al, 2022). Keluhan nyeri lutut ini dapat menurunkan produktivitas petani karena keterbatasan gerak, meningkatkan biaya perawatan kesehatan, kualitas hidup yang menurun karena nyeri kronis, serta meningkatkan risiko cidera berulang sampai dengan kecacatan.…”
Section: Pendahuluanunclassified